Determinants of Green Total Factor Productivity in Indonesia: The Role of Environment in Economic Development with A Parametric Approach - Pradiana, Bella; Wahyuni, Krismanti Tri (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
Environmental degradation occurs during economic development. Green Total Factor Productivity (TFP) was developed by incorporating environmental variables into traditional TFP to measure the efficiency of using technology to produce output, while balancing environmental quality. This study aims to determine the general description of economic development in Indonesia in 2015–2021, estimate economic development, and calculate Green TFP in Indonesia in 2015–2021, know the general description of Green TFP, and the variables that are thought to influence Green TFP in Indonesia in 2015–2021. 2021 and analyzed the variables influencing Green TFP in Indonesia in 2015–2021. The estimation results of the economic growth model showed a trade-off between economic growth and environmental quality in Indonesia. The Green TFP results for provinces in Indonesia are obtained using the Cobb-Douglas production function and panel data regression. The value of Green TFP in Indonesia is stagnant, at approximately 0.002. The analysis of variablesaffecting Green TFP using panel data regression shows that HDI, government spending on education, electricity consumption, industry share, capital structure, and trade openness have significant effects on Green TFP.